The Implementation of Income Tax Article 22 on Goods Purchased by the General Affairs Section of the Regional Secretariat of Jember Regency - Farhan, Ahmad; Imam, Muhammad Khoirul; Siswanto, Adil (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research paper aims to assess the compliance of the Regional Secretariat of Jember Regency with the Ministry of Finance Regulation 59/PMK.03/2022 on calculating, collecting, depositing, and reporting taxes on purchased goods, focusing on the implementation of Income Tax Article 22.Method: The study uses Action Research with qualitative methods, gathering data through observations and interviews with staff in the General Affairs Section to evaluate their tax practices.Practical Applications: Findings indicate effective calculation and collection of Income Tax Article 22 but highlight a need for clearer regulations regarding reporting Income Tax Returns (SPT). These insights can enhance tax compliance and improve public service delivery in local governance.Conclusion: The study confirms that the General Affairs Section complies with the Ministry of Finance Regulation in calculating and collecting Income Tax Article 22. However, it identifies a regulatory gap in SPT reporting, contributing to a broader understanding of local tax compliance issues.